2018
DOI: 10.1103/physrevlett.120.193901
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Focal Modulation Microscopy

Abstract: We demonstrate nonlinear focal modulation microscopy (NFOMM) to achieve superresolution imaging. Traditional approaches to superresolution that utilize point scanning often rely on spatially reducing the size of the emission pattern by directly narrowing (e.g., through minimizing the detection pinhole in Airyscan, Zeiss) or indirectly peeling its outer profiles [e.g., through depleting the outer emission region in stimulated emission depletion (STED) microscopy]. We show that an alternative conceptualization t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…We used two‐view RL deconvolution in FED microscopy shown in Zhao et al . (). In this simulation, subtractive factor C is set to 0.9, and the diameter of pinhole D is set to 1.5 AU.…”
Section: Simulations and Discussionmentioning
confidence: 97%
“…We used two‐view RL deconvolution in FED microscopy shown in Zhao et al . (). In this simulation, subtractive factor C is set to 0.9, and the diameter of pinhole D is set to 1.5 AU.…”
Section: Simulations and Discussionmentioning
confidence: 97%
“…It maximizes the capabilities of Fourier domain OTF fusion of multiple emission PSFs in the spectral regime to improve the entire imaging quality, which can recover the otherwise hidden spatial information during the single beam scanning and confocal detection process. Compared with the temporal domain modulation of excitation modality that requires switching illumination pattern [ 43 ] or laser mode [ 44 ] with dual excitations procedure, the single scan method is simple, fast, and stable, and can avoid the use of the additional optical components and procedures in correcting the sample drifts between multiple sequential recordings. The single‐beam scanning mode using a simplified optics setup is compatible with the standard commercial or lab‐based laser scanning microscopes, and therefore may overcome the current bottleneck issue associated with the system complexity and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that UCNPs with unique nonlinear optical response and saturation properties can be developed as novel fluorescent probes, [ 32–37 ] especially for the sub‐diffraction imaging technologies. [ 38–41 ] Most recently, the dual NIR (980 nm excitation and 800 nm emission) working wavelength in UCNPs shows its utility in deep tissue super‐resolution imaging, [ 18,42 ] but the doughnut‐shaped PSF induces artifacts during the deconvolution process, as a certain band of frequency has been lost in the Fourier domain, [ 43,44 ] affecting the imaging quality. Ideally, simultaneously obtaining diverse PSFs using a simple setup, maximizing spatial information in the Fourier domain, would enhance the spatial resolution and overall imaging quality.…”
Section: Introductionmentioning
confidence: 99%
“…Sample handling approach, like expansion microscopy 6 , special inorganic nanoparticles labelling [7][8][9] , can be used to empower a conventional microscope with super-resolution imaging. Moreover, based on the optical geometry of confocal microscopy, the achieved developments such as image scanning microscopy 10,11 , focal modulation microscopy 12 , confocal rescan microscopy 13 has obtained remarkable resolution enhancement with the assistance of the special optical geometry and array detector. Nonetheless, the sample handling approach and the instrument modification approach still rely on complex sample processing process or special optical components and/or special inorganic nanoparticles with low labeling density.…”
Section: Mainmentioning
confidence: 99%